Decentralized and privacy-aware management of energy storage systems and electric vehicles in smart grids - Singh, Anshuman (Nanyang Technological University, 2024)
Optimal operation of battery energy storage systems (ESS) and electric vehicles (EVs) is vital for integrating distributed energy resources. The conventional approach of centralized control in managing these devices encounters formidable challenges such as a large number of decision variables, communication needs, and privacy concerns. Moreover, it may not fully address device health, temperature, and economic sustainability. Decentralized control frameworks offer distinct advantages over their centralized counterparts, particularly by affording devices a degree of autonomy, ensuring safe operation and being scalable. Nonetheless, they are not devoid of their own set of challenges. Decentralized decision-making predicates upon local information which may lead to potential violations of grid constraints. Additionally, coordinating with peers can be challenging for smaller-scale ESS and EV charging stations with limited technical capabilities. One potential solution is the use of aggregator systems, but this can raise privacy concerns when the ESS or EV shares its thermal model with the aggregator. The present thesis aims to investigate various decentralized management schemes, with a particular focus on privacy-aware considerations, to optimize the operation of ESS and EVs while concurrently ensuring that the grid states are within the specified limits.